Perselisihan antara â€œAkuâ€ dengan â€œSayaâ€ pada Diri Calon Pendeta Unshakeable Church Bali - Sari Sinaga, Putri Ratna; Nugroho, Wahyu Budi; Krisna Aditya, I Gst. Ngr. Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Dispute between "I" and "me" uses the self of the prospective pastor to minimize and anticipate pastors who are involved in social problems. The purpose is to explain the process of disagreement between "I" and "me" in the candidate for pastor and analyze ideal self-concept of the ideal pastor in his status and role as the pastor of the Bali Unshakeable Church. This research uses George Herbert Mead's self-concept and uses a descriptive-exploratory research method using a qualitative approach. The results show that various socialization media have their respective values and norms that apply and have the potential to create clashes that cause disputes within prospective pastors and affect them. The ideal pastor in the Bali Unshakeable Church is to imitate Jesus and have the fruit of the Spirit, while the role of the pastor is to preach in front of the pulpit and lead the life of the congregation.